Hydrogen-Rich Water as a Novel Therapeutic Strategy for the Affective Disorders Linked with Chronic Neuropathic Pain in Mice - Maria Martínez-Serrat; Ignacio Martínez-Martel; Santiago Coral-Pérez; Xue Bai; Gerard Batallé; Olga Pol (Antioxidants, 2022)
Neuropathic pain manifested with allodynia and hyperalgesia usually becomes a chronic condition accompanied with mood disorders. Clinical therapies for neuropathic pain are still unsatisfactory with notable side effects. Recent studies have reported the protective role of molecular hydrogen (H2) in different diseases including neurological disorders, such as Alzheimer’s as well as its antidepressant activities in animals with chronic stress. This study explored the effects of treatment with hydrogen-rich water (HRW) in male mice with neuropathic pain induced by the chronic constriction of the sciatic nerve (CCI) and the accompanying affective deficits. The likely pathways implied in the HRW analgesic activity, as well as the interaction between heme oxygenase 1 (HO-1) enzyme and H2 during neuropathic pain were also studied. The results showed: (i) the inhibitory effects of the repetitive treatment with HRW on the allodynia and hyperalgesia provoked by CCI; (ii) the anxiolytic and antidepressant actions of HRW in animals with neuropathic pain; (iii) the contribution of the antioxidant enzymes (HO-1 and NAD(P)H: quinone oxidoreductase 1) and the ATP sensitive potassium channels in the painkiller activities of HRW during neuropathic pain; (iv) a positive interaction between the HO-1 and H2 systems in inhibiting the CCI-induced neuropathy; and (v) the antioxidant, antinociceptive, anti-inflammatory and/or antiapoptotic features of HRW treatment in the dorsal root ganglia and/or amygdala of sciatic nerve-injured mice. This study demonstrates new protective actions of H2 and suggests that treatment with HRW might be an interesting therapeutic strategy for chronic neuropathic pain and its associated mood disorders.